2021
DOI: 10.1007/s42247-020-00150-w
|View full text |Cite
|
Sign up to set email alerts
|

Smart materials-integrated sensor technologies for COVID-19 diagnosis

Abstract: After the first case has appeared in China, the COVID-19 pandemic continues to pose an omnipresent threat to global health, affecting more than 70 million patients and leading to around 1.6 million deaths. To implement rapid and effective clinical management, early diagnosis is the mainstay. Today, real-time reverse transcriptase (RT)-PCR test is the major diagnostic practice as a gold standard method for accurate diagnosis of this disease. On the other side, serological assays are easy to be implemented for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 200 publications
(237 reference statements)
0
26
0
Order By: Relevance
“…IgM antibodies are detected within the first several weeks, while IgG antibodies are detected later. Detection of antibodies confirms past contact with the virus; unfortunately, the absence of antibodies does not provide a basis for the exclusion of past infection [41].…”
Section: Diagnosticsmentioning
confidence: 96%
See 1 more Smart Citation
“…IgM antibodies are detected within the first several weeks, while IgG antibodies are detected later. Detection of antibodies confirms past contact with the virus; unfortunately, the absence of antibodies does not provide a basis for the exclusion of past infection [41].…”
Section: Diagnosticsmentioning
confidence: 96%
“…Moreover, the use of nanoparticle-based markers can enable the study of the mechanism by which viruses infect host cells. Among a variety of nanomaterials that could be used for virus detection, gold nanoparticles and graphene seem the most promising [41,49].…”
Section: Adaptation Of New Technologies For Detection Of Sars-cov-2mentioning
confidence: 99%
“…The most frequently used nanomaterial for FET sensing platforms is graphene, characterized by high electronic conductivity, carrier mobility, and the large specific surface area, which provides an optimal environment for ultrasensitive detection. [447,448] Ono et al [449] demonstrated the graphene FET functionalized with sialoglycan for the selective detection of the influenza virus. It exhibited very high sensitivity and specificity toward two lectins derived from Sambucus sieboldiana and Maackia amurensis used as alternatives to the human and avian virus.…”
Section: Electrochemical Nanobiosensorsmentioning
confidence: 99%
“…Erdem et al [14] demonstrated that COVID-19 has caused a serious of devastating effects on global health system, which needs rapid and aggressive solutions to quickly curtail the spread. The authors noted that effective clinical management and implement strategies through prompt diagnostic techniques are a mainstay.…”
Section: Application Of Sensors and Biosensors For Monitoring And Detection Of Covid-19mentioning
confidence: 99%